Saṅgahavatthu Principles of School Administrators Affecting Organizational Culture of Schools Under Bangkok Metropolitan Administration, Southern Krungthon Group - Ninlapong, Janjira; Chiinathattiyo, Phramaha Kraiwan (Journal of Dhamma for Life, 2026)
This thesis aimed to study (1) Saṅgahavatthu Principles of School Administrators under Bangkok Metropolitan Administration, Southern Krungthon Group, (2) the organizational Culture of Schools under Bangkok Metropolitan Administration, Southern Krungthon Group, and (3) Saṅgahavatthu Principles of School Administrators Affecting Organizational Culture of Schools under Bangkok Metropolitan Administration, Southern Krungthon Group. The population for this study consisted of 70 schools under the Bangkok Metropolitan Administration, Southern Krungthon Group. The sample included 59 schools, with 236 respondents comprising school directors, deputy directors or academic heads, and teachers. Research instruments included in-depth interviews and a questionnaire. Data were analyzed using statistical software. Descriptive statistics (Frequency, Percentage, Mean, and Standard Deviation) and Multiple Regression Analysis were used for hypothesis testing. The results of this research were as follows: 1. Saṅgahavatthu Principles of School Administrators under Bangkok Metropolitan Administration, Southern Krungthon Group, was at the highest level overall. The principle practiced most was the administrators’ Atthacariya (beneficial actions), followed by the administrators’ Piyavaca (kind speech), and the administrators’ Dana (liberality). 2. The organizational Culture of Schools under Bangkok Metropolitan Administration, Southern Krungthon Group was also at the highest level overall. The highest-rated dimension was criteria of success, followed by dominant characteristics, and organizational leadership. 3. Saṅgahavatthu Principles of School Administrators affected the organizational Culture of Schools under Bangkok Metropolitan Administration, Southern Krungthon Group, with statistical significance at the .01 level, and the predictive equation can be written as follows: Forecast equations in raw score form Y ̂ = 1.017+ .198(X2) + .177(X3) + .344(X4) Forecast equations in standard score form Z ̂ = .236(X2) + .218(X3) + .412(X4)